Motivasi Narapidana Menjadi Tahanan Pendamping (Tamping) di Lembaga Pemasyarakatan Kelas IIA Jember - Ajeng Cahya Safitri (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
A support inmate (Tamping) is an inmate entrusted by staff to assist with certain operational activities within a correctional facility. The presence of these support inmates plays a crucial role in supporting the smooth operation of rehabilitation and daily activities at the facility, particularly amid overcrowded conditions. An inmate’s decision to become a Tamping is driven by various underlying motivations. Therefore, this study aims to describe the motivations of inmates who choose to become Tamping at the Class IIA Jember Correctional Institution. The research findings indicate that the motivation of inmates to become tamping is shaped by two motives of action, according to Alfred Schutz: the “Because Motive” and the “In-Order-To Motive.” The “Because Motive” arises from the inmates’ experiences during their incarceration, such as monotonous routines, boredom, limited freedom of movement, and the influence of the social environment, which drives them to seek more meaningful activities. Consequently, the “In-Order-To Motive” emerges, which relates to the goals they aim to achieve through the status of being a prison guard, such as engaging in more productive activities, gaining greater freedom of movement, earning the trust of staff, and receiving bonuses. Thus, the motivation of inmates to become prison guards is not merely driven by the limitations of prison life but is aimed at achieving a more active, productive, and meaningful life during their incarceration. The findings of this study indicate that serving as a tamping is not merely a form of assistance to staff but also serves as a means for inmates to build meaning, social standing, and autonomy within the prison.
Finalisasi 16 Juli 2026_Yudi
Keywords: Motivation; Inmates; Companion Detainees (Tamping)